THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CLASS IIA BENGKULU CORRECTIONAL INSTITUTION - Ladico, M. Ejo Pratama; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine how work motivation affects employee performance at the Bengkulu Class IIA Correctional Institution. The research method used is a quantitative approach with data collection through questionnaires distributed to 89 employees. The data were analyzed using normality test, simple linear regression test, significance test, and determination test processed using IBM SPSS software version 25. The results showed that there is a significant positive influence between work motivation and employee performance. This finding indicates that increasing work motivation through various programs and policies that support it can improve employee performance in correctional institutions. This research is expected to provide insights for management in designing more effective strategies to improve employee motivation and performance in the institution. Keywords: Work Motivation; Employee Performance; Class IIA Correctional Institution Bengkulu